Improving Student Learning Independence by Using Models Discovery Learning at School - Rediyono (Jurnal Penelitian Pendidikan IPA, 2025)
This research is motivated by the low independence of students' learning in creative product subjects in class XI SMK Putra Bangsa Bontang, East Kalimantan. One solution to overcome this problem is to use the Discovery Learning learning model. The purpose of this study is to describe the improvement of students' learning independence by using the Discovery Learning learning model in students of XI SMK Putra Bangsa Bontang, East Kalimantan. The research method is Classroom Action Research (CAR) which is carried out in two cycles. Each cycle consists of two meetings and four stages, namely planning, implementation, observation, reflection, and the research time is carried out until August. The subjects of this study were students of class XI SMK Putra Bangsa Bontang, East Kalimantan. Totaling 15 people consisting of 8 male students and 7 female students. The results of the study showed that there was an increase in students' learning independence from pre-action to cycle I by 10.80%. The increase in students' learning independence also showed an increase from cycle 1 to cycle 2 by 24.78%. The conclusion of this study is that there was an increase in students' learning independence overall by 35.58%. Discovery Learning learning must continue to be carried out to improve the learning independence of vocational school students. Teachers need ongoing guidance to be able to apply the Discovery Learning model according to the recommended steps.